Hardware Implementation of Shunt APF Using Modified Fuzzy Control Algorithm with STM32F407VGT Microcontroller - Anjana, Pradeep; Gupta, Vikas; Tiwari, Harpal; Gupta, Nitin; Bansal, Ramesh (Electric power components and systems, 2016)
This article presents a modified fuzzy controller (MFC) to generate a reference signal for the control algorithm to drive the shunt active power filter (SAPF) for improving the power quality of a microgrid at the distribution end. The proposed MFC, based on the alive-and-kicking behavior of the system, is used to regulate the DC-link voltage of the SAPF. The MFC is implemented through the general dynamic behavior of a process with introducing the new rules set. It is compared with the PI controller for evaluation of optimal steady-state, dynamic, and transient performance of SAPF, namely the reactive power and DC voltage control. The effectiveness of the proposed controller is tested on non-linear loads using a hardware prototype. The STM32F407VGT (ARM Ltd., San Jose, California, USA) processor is used to interface algorithm with the hardware setup. The results of the proposed controller scheme are promising and are compared with MATLAB (The MathWorks, Natick, Massachusetts, USA) simulation results. The system is capable for minimizing current harmonics, reactive power and improving the power factor. Also, the advantage of the STM32F407VGT over the Digital Signal Processor (Texas Instruments, USA) is introduced. The performance of the proposed controller is better in comparison with conventional controller.